E-Government and Bureaucratic Reform: A Study in the Regional Government of West Nusa Tenggara - Hidayatullah, Hidayatullah; Hadi , Ayatullah; Lestanata, Yudhi (Journal of Social and Policy Issues, 2025)
This study aims to analyze the implementation of e-government as part of bureaucratic reform at the local government level. The research method used is qualitative and uses NVivo 12 Plus to analyze the data. The results show that implementing e-Government in West Nusa Tenggara (NTB) Province has shown significant progress as an integral part of bureaucratic reform. Various digital platforms such as NTB Satu Data, NTB Care, SIPD, and SPBE-based services have successfully increased efficiency, transparency, and accountability in governance. The increase in the SPBE index value nationally and through internal assessments demonstrates a strong commitment from the local government to building an integrated digital government system that is responsive to public needs. NTB continues to encourage digital transformation with various strategies such as ICT training for civil servants, strengthening networks and data centers, and developing artificial intelligence-based applications. This step proves that digitalization is focused on providing public services and enhancing the internal capacity of the bureaucracy. NTB has positioned e-Government as a strategic instrument in realizing a more adaptive, professional, and participatory bureaucracy. By maintaining this positive trend and overcoming existing obstacles, NTB has great potential to become a model for best practices in digital government implementation in Indonesia, while accelerating the achievement of the vision of a clean, effective, and serving national bureaucratic reform.